Кількісні характеристики просторових іменників-антонімів - Гончарук, Світлана Вікторівна; Honcharuk, S. V. (Національний університет "Острозька академія", 2010)
Стаття присвячена дослідженню частоти просторових іменників-антонімів. Автор аналізує абсолютні частоти членів антонімічних пар за допомогою статистичних методів. The article is devoted to the investigation of frequent characteristics of spatial nouns-antonyms. The author analyses absolute frequencies of the members of antonymous pairs with the help of statistical methods.
Quantitative characteristics of spacial nouns- antonyms
Keywords: кількісні характеристики; quantitative characteristics; абсолютна частота; absolute frequency; хі-квадрат; chi-square